Understanding Education History, Politics and Practice - Kemmis, Stephen (Springer Texts in Education, 2018)
This short book provides an introduction to the study of education, outlining the dual purpose of education - to help people live well and to help develop a world worth living in. It argues that education initiates people into forms of understanding, modes of activity, and ways of relating to each other and the world that not only help individuals to live good lives, but also help secure a culture based on reason, productive and sustainable economies and environments, and just and democratic societies. Subsequent chapters address the history of education in the West; explore how education reproduces the practices and forms of life in societies and groups, and also how it transforms them; and introduce the theory of practice architectures to explain what practices are composed of, and how they are enabled and constrained by local and more general conditions and circumstances. The book closes by showing how the theory of practice architectures unfolds to offer a theory of education - a theory that underpins the definition of education offered at the start of the book. Understanding Education is essential reading for anyone interested in the theory and practice of education.